Partnership approaches to the evaluation of complex policy initiatives: Qualitative research as key to building effective relationships. (19th July 2018) - Turner‐Halliday, Fiona; Welch, Vicki; Bryce, Graham; Forde, Matt; Cotmore, Richard; Wilson, Phil; Fitzpatrick, Bridie; Watson, Nicholas; Minnis, Helen
Abstract : We argue that major health and social care policy initiatives are not too complex for randomised controlled trial (RCT) methodology and illustrate this using the example of the Best Services Trial (BeST ? ): a RCT of an infant mental health intervention for maltreated children. We suggest that qualitative research, as a core part of the trial process from conception and development through to implementation and evaluation, is crucial in building, understanding and strengthening the partnership required to drive such a complex trial. Data pertinent to trial implementation demonstrate the iterative nature of the process whereby stakeholders are consulted and their views influence the conduct of the trial. Here we reflect on the bi‐directional relationship between qualitative data collection and partnership‐working in a trial. For very complex trials to be possible, significant resource needs to be available for the qualitative component. Key Practitioner Message: Qualitative research is key to understanding, building and strengthening partnership approaches to researching complex interventions; Qualitative research is vital to supporting randomised controlled trials involving multiple sectors; Qualitative research provides essential explanatory power to outcome data in research .